(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: chronic myeloid leukemia is one of the major diseases, which cause death worldwide. Tyrosine kinase is responsible for uncontrolled cell growth and block its function. Its inhibition is a promising route to control the out of control grow of cells. The purpose of our study involves docking of human Abl kinase with seven ciprofloxacin derivatives and the comparison of results free energy binding with positive control (Imatinib).Methods: the present study aims to examine the interactions between human Abl kinase(2HYY) domain retrieved from protein data bank and seven ciprofloxacin derivatives in comparison with imatinib as a reference. The analysis was performed using Autodock vina Implicated in the PyRx 0.8 tool.Results: docking revealed that, according to their free binding energy imatinib still have the lowest binding energy followed by CHOCP and MPCP. In silico ADMET predictions revealed that except DMOCP all other compounds had toxic effects.Conclusion: these compounds may not serve as a potential inhibitor due to their high free energy binding and their toxicity in comparison with imatinib.